Abattoir-based survey of contagious bovine pleuropneumonia in cattle in Turkey - Çetinkaya, B; Öngör, H; Karahan, M; Kalender, H; Lorenzon, S; Thiaucourt, F (British Veterinary Assoc, 2003)
Blood samples collected from 945 cattle at four local abattoirs in Turkey were examined for contagious bovine pleuropneumonia (CBPP) by the complement fixation test (CFT) and competitive ELISA (cELISA). In addition, the carcases of the animals were examined macroscopically at the abattoirs and 62 lung samples which had lesions suggestive of CBPP were collected for bacteriological culture. To identify suspicious isolates the PCR was used in addition to the routine biochemical tests. By the CFT, two of the 945 serum samples were seropositive, and by the cELISA, four of them were seropositive. In the bacteriological culture of the lungs, growth was observed in 18 (29 per cent) of the samples by the observation of turbidity in the broths. However, when these broths were inoculated into an agar base, growth was observed in only three (4-8 per cent) samples. These isolates were identified as Mycoplasma species on the basis of biochemical tests. in the PCR analysis Of DNA extracted from the broths, none of the isolates was identified as Mycoplasma mycoides subspecies mycoides small colony or one of the members of the M mycoides cluster, but amplification was obtained in only eight (44-4 per cent) of 18 samples, using Mycoplasma-genus specific primers. These DNA samples were examined further with primers specific to 165 rRNA and were then sequenced and compared with the databanks; DNA homologies at different levels were observed in five samples, with Mycoplasma alkalescens, Mycoplasma canadense, Mycoplasma bovis and Mycoplasma bovigenitalium.
Keywords: Mycoplasma-Mycoides Cluster; Polymerase-Chain-Reaction; Ribosomal-Rna Genes; 16S Rdna Sequences; et-Al. 1989; Subspecies Mycoides; Mastitic Milk; Pcr; Sc; Diagnosis